Controlling of semiconductor/metal junction barrier by 5,10,15,20- tetraphenyl-21H,23H-porphine ruthenium(II) carbonyl - Yakuphanoğlu, Fahrettin (National Institute of Optoelectronics, 2007)
The electrical characteristics of RuP/p-Si/Al junction barrier have been investigated by current-voltage and capacitance-voltage characteristics. A deviation in l-V characteristic of the diode is observed due to effect of series resistance and interfacial layer. RuP/p-Si/Al diode is a metal-interfacial layer-semiconductor type diode with calculated electronic parameters (ideality factor, series resistance and barrier height; n=1.95, Rs=6.25 k? and ?B=1.23 eV). The obtained barrier height and ideality factor values of RuP/p-Si/Al diode at the room temperature is significantly larger that that for the conventional Al/p-Si Schottky diode. It is evaluated that RuP organic layer modifies electronic properties of metal-semiconductor devices based on p-Si.
Keywords: Metal-semiconductor contact; Organic semiconductor; Series resistance